Geodetic auscultation on chimneys at "Johnson Matthey" - Bogdanovski Zlatko, Srbinoski Zlatko (MASE - Macedonian Association of Structural Engineers, 2017)
The determination of geometrical deformations on engineering structures is a very common problem of the surveying experts. For this purpose, use of modern geodetic measuring technology as well as appropriated measuring methods and calculations of geodetic measurements are more than necessary. The geodetic auscultation on high structures encompasses a series of specific measurements defining their geometry and spatial deformations. In this paper is shown the concept and basic results of the geodetic auscultations on the chimneys at the industrial complex “JOHNSON MATTHEY” - which is located at economic zone “Bunardzik” near Skopje.
Геодетска оскултација на оџаците во "Johnson Matthey"
Keywords: chimneys, geodetic auscultation, geometric deformations